Comparison of Echocardiography and Computed Tomography/Magnetic Resonance Imaging for Assessing of Pulmonary Vein Stenosis in Children - Mykychak, Y.; Kozhokar, D.; Yusifli, I.; Morkovkina, A.; Tammo, R.; Yemets, I. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Pulmonary vein (PV) stenosis is a rare disease with high recurrence and mortality rates. Objective. This study was aimed to evaluate the diagnostic accuracy of echocardiography versus cross-sectional modalities. Material and methods. Our study includes 11 consecutive patients who underwent a comprehensive PV anatomy assessment between April 2018 and June 2019 at Ukrainian Children’s Cardiac Center, Kyiv. Echocardiographic studies of each pulmonary vein followed by computed tomography (CT) or magnetic resonance imaging (MRI) were performed in all patients. A total of 27 CT/MRI studies were performed. Results. There were four patients whose echocardiography findings were completely confirmed by CT/MRI method. In some patients significant stenosis was underestimated by echocardiography. Sensitivity and specificity were 86.4 and 88.9 for echo, as well as 100 and 94.4 for CT/MRI, respectively. Conclusion. This study recognizes the limitations of echocardiography as an imaging tool for pulmonary veins morphology assessment. Cross-sectional studies overcome these limitations and provide excellent morphological as well as functional (MRI) evaluation of pulmonary veins.